2006
DOI: 10.3998/ark.5550190.0007.c18
|View full text |Cite
|
Sign up to set email alerts
|

Convenient synthesis of new functionalized cyclopropanes from monoterpenic olefines

Abstract: Five new cyclopropyl-ketoacids were prepared in good yields from monoterpenic olefines using solid-liquid phase transfer catalysis (SL-PTC) dichlorocyclopropanation reaction followed by oxidative cleavage with RuCl 3 -NaIO 4 system. The nonchlorinated cyclopropanes were obtained by sodium/methanol reduction of the corresponding gem-dichlorocyclopropanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…gem-Dichlorocyclopropyl derivatives of limonene, terpinolene and γ-terpinene were synthesized using NaOH and benzyltriethyl ammonium chloride (TEBAC) in CHCl 3 at room temperature affording monocyclopropanated products in good yield (Scheme 1). 10 oxirane ring of the resulting product 6 was cleaved oxidatively using the RuCl 3 -NaIO 4 catalytic system; crystallization of the product led to the respective diastereomers of the dihalocyclopropane ring system 7.…”
Section: Phase Transfer Catalysis In the Synthesis Of Gem-dihalocyclo...mentioning
confidence: 99%
“…gem-Dichlorocyclopropyl derivatives of limonene, terpinolene and γ-terpinene were synthesized using NaOH and benzyltriethyl ammonium chloride (TEBAC) in CHCl 3 at room temperature affording monocyclopropanated products in good yield (Scheme 1). 10 oxirane ring of the resulting product 6 was cleaved oxidatively using the RuCl 3 -NaIO 4 catalytic system; crystallization of the product led to the respective diastereomers of the dihalocyclopropane ring system 7.…”
Section: Phase Transfer Catalysis In the Synthesis Of Gem-dihalocyclo...mentioning
confidence: 99%
“…For background to and applications of dichlorocyclopropane derivatives, see: Hirota et al (1996); Kü nzer et al (1996); Ziyat et al (2004);Fedorynski (2003). For the synthesis and structures of optically active dihalogenocylopropanes reported by our group, see: Ziyat et al (2002); Boualy et al (2009); Ziyat et al (2006). For puckering parameters, see: Cremer & Pople (1975).…”
Section: Related Literaturementioning
confidence: 99%
“…These compounds have found wide applications as substrates for the synthesis of many class of compounds such as pyrethroides (Ziyat et al, 2004), benzocyclopropenes or cyclopentadiene derivatives (Fedorynski, 2003), which are not easily obtained using other starting materials. As a part of our ongoing research aimed at the synthesis of optically active dihalogenocylopropanes from terpenes (Ziyat et al, 2002;Ziyat et al, 2004;Boualy et al, 2009;Ziyat et al, 2006), the title compound has been prepared and its crystal structure is reported herein.…”
Section: Crystal Datamentioning
confidence: 99%
“…dihydrocarvone [3,4] and 1,2-limonene oxide. Because the latter compound is easily prepared from naturally available limonene [5], the interest for direct syntheses of carvenone from 1,2-limonene oxide has been increasing [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. However, most of the related reports showed that the selectivity towards carvenone was not good as expected.…”
Section: Introductionmentioning
confidence: 99%